Media irritability: exploration of human rights issues in Indonesia during 2009-2019 - Senja Yustitia; Nunung Prajarto; Budi Irawanto (Penerbit Universiti Kebangsaan Malaysia, 2023)
As an observing system, the media creates a construction of reality. In Indonesia, one of the interesting and crucial realities is human rights since it is associated with the state of democracy. This study is aimed at exploring the function of media irritability concerning human rights issues in Indonesia during the 2009-2019 period through a series of frames that emerged on the news. The main research question addressed in the current study refers to how media framing of human rights issues in Indonesia is utilized by the media to illustrate the state of human rights. The human rights issue selected is civil and political rights in the 2009-2019 period reported by two media, namely Koran Tempo and Kompas newspapers. Frame analysis was used as a method with a strategic frame analysis (SFA) approach. All the research results were analyzed using the media irritability concept, which is one of the key ideas of Niklas Luhmann’s System Theory. This research results indicate that, generally speaking, human rights frames in Indonesia did not undergo any changes between 2009 and 2019. Human rights had been framed as a mandate or agenda of the reform. The framing of human rights conditions in Indonesia remained stagnant without any progress. The function of media irritability has yet to be significantly observed. The framing of human rights, which tended to be stagnant, remains incapable of mobilizing other systems to resonate with human rights issues.